Analisis Kinerja Struktur Gedung Perkantoran Pabrik Pupuk Gresik dengan Pembebanan Gempa Berdasarkan SNI 1726:2019 terhadap Simpangan Antar Lantai dan Pengaruh P-Delta - Muzaki, Achmad; Trimurtiningrum, Retno (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Earthquakes are natural phenomena caused by natural events. The strength of an earthquake can be measured using a seismometer. The most commonly used scale to measure the strength of an earthquake is the Richter scale. The amount of demage caused by an earthquake is not only determined based on its strength, but is also measured by the area where the earthquake occurs. The depth of an earthquake that occurs from within the earth can also affect the potential damage. Eatrhquakes are located close to the groound surface, so they can have significant destructive properties. Large earthquake can usually trigger aftershocks, so they can be overcome using temporal processes.This research carried out an analysis of story drift and the influence of P-Delta on the reinforced concrete structure of the office building PT. Pupuk Lapan Harsa based on SNI 1726:2019. With the planning concept using the help of SAP2000 software.The results of the analysis of the Gresik fertilizer factory office building were delcared safe with a story drift in the x-axis ( ) in the amount of 10,95 mm up to 31,85, in the y-axis ( ) in the amount of 10,95 mm up to 31,85 mm. Meanwhile, the value of the influence of P-Delta in the x-axis ( ) in the amount of 0,007 up to 0,036, in the y-axis ( ) in the amount of 0,007 up to 0,036. Earthquakes are natural phenomena caused by natural events. The strength of an earthquake can be measured using a seismometer. The most commonly used scale to measure the strength of an earthquake is the Richter scale. The amount of demage caused by an earthquake is not only determined based on its strength, but is also measured by the area where the earthquake occurs. The depth of an earthquake that occurs from within the earth can also affect the potential damage. Eatrhquakes are located close to the groound surface, so they can have significant destructive properties. Large earthquake can usually trigger aftershocks, so they can be overcome using temporal processes.This research carried out an analysis of story drift and the influence of P-Delta on the reinforced concrete structure of the office building PT. Pupuk Lapan Harsa based on SNI 1726:2019. With the planning concept using the help of SAP2000 software.The results of the analysis of the Gresik fertilizer factory office building were delcared safe with a story drift in the x-axis ( ) in the amount of 10,95 mm up to 31,85, in the y-axis ( ) in the amount of 10,95 mm up to 31,85 mm. Meanwhile, the value of the influence of P-Delta in the x-axis ( ) in the amount of 0,007 up to 0,036, in the y-axis ( ) in the amount of 0,007 up to 0,036.